2007
DOI: 10.1007/s11433-007-0020-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermoluminescence in Li2B4O7 phosphors doped with Cu, Ag and Mg

Abstract: Li 2 B 4 O 7 (LBO):Cu,Ag,Mg phosphors have been prepared by the sintering technique.The roles of the Ag and Mg dopants in the phosphors have been studied using the methods of thermoluminescence (TL) glow curves and TL 3D spectra. The results indicated that proper concentrations of Ag and Mg can enhance the TL of LBO:Cu. It was also indicated that the intensity of TL peak at ~130 is reduced with ℃ the increasing Ag concentration, and enhanced with the increasing Mg concentration.From the TL 3D spectra, three em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The results, as shown in Figure 6(a), are similar to that illustrated in ref. [10]. The curves show that the maximum TL response is around 380 nm and can be deconvoluted by 3 Gauss peaks (λ 1 = 425 nm, 1 ν = 23530 cm −1 ; λ 2 = 381 nm, 2 ν =26250 cm −1 ; λ 3 = 354 nm, 3 ν = 28250 cm −1 ) (Figure 6(b)).…”
Section: Tl Spectramentioning
confidence: 94%
See 2 more Smart Citations
“…The results, as shown in Figure 6(a), are similar to that illustrated in ref. [10]. The curves show that the maximum TL response is around 380 nm and can be deconvoluted by 3 Gauss peaks (λ 1 = 425 nm, 1 ν = 23530 cm −1 ; λ 2 = 381 nm, 2 ν =26250 cm −1 ; λ 3 = 354 nm, 3 ν = 28250 cm −1 ) (Figure 6(b)).…”
Section: Tl Spectramentioning
confidence: 94%
“…The emission spec- trum of lithium tetraborate doped with Cu is around 360 nm [2] and the emission spectrum of LBO:Cu,In is around 420 nm [7,8] . This effect is caused by the preparation procedures or such factors as metalline impurity which can change the relative intensity among the 3 peaks [10] . Components of the 3 peaks in the spectra of Li 2 B 4 O 7 :Cu, Ag,P phosphors are reported in ref.…”
Section: Tl Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Modifying the structure of the host lattice by introducing hetero-cations may effectively improve the luminescent intensity of a phosphor [7][8][9][10][11][12]. For example, Li et al [7] studied the influence of Ba 2+ and Ca 2+ impurities on the cathodoluminescent spectrum of Sr 5 (PO 4 ) 3 Cl:Eu 2+ .…”
mentioning
confidence: 99%
“…For example, Li et al [7] studied the influence of Ba 2+ and Ca 2+ impurities on the cathodoluminescent spectrum of Sr 5 (PO 4 ) 3 Cl:Eu 2+ . Xiong et al [8] found that appropriate concentrations of Ag and Mg can enhance the thermoluminescence of Li 2 B 4 O 7 :Cu. In this paper, we report a significant shift and increase in the excitation intensity of the charge transfer band in BaZr(BO 3 ) 2 :Eu 3+ phosphors after Si 4+ doping.…”
mentioning
confidence: 99%